Water Pollution Index and The Distribution of Waterborne Diseases on The East Flood Canal, Semarang City : An Analysis Spatial - Yura Witsqa Firmansyah; Onny Setiani; Yusniar Hanani Darundiati; Tri Joko; Mursid Raharjo (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
High environmental health quality status is an environmental condition that needs to be preserved. Poor environmental health quality is closely related to the level of heavy pollution status and the high incidence of waterborne disease. In 2018 there were 25 rivers with heavy pollution status in Indonesia and the condition is worsened in 2019 with as many as 38 rivers in the condition of heavy pollution status. Water pollution can be a factor in the emergence of waterborne diseases such as diarrhea, typhoid and leptospirosis. This study aimed to provide an overview of the water pollution index and the incidence of waterborne disease on the Semarang East Flood Canal with a spatial modelling approach. This research was a spatial analysis approach. The type of data in this study is quantitative with retrieval 6 sampling points on the east bank of The Canal Flood which was then analyzed with spatial-Gis modelling. Parameters for the water pollution index were total coliform, faecal coliform, dissolved oxygen, and anionic detergent. From the results of the calculation of the water pollution index, sample points 1-6 (T1-T6) are categorized with mild pollution status. However, when viewed from each parameter, there are total coliform, faecal coliform, dissolved oxygen parameters that exceed the quality standard. Existing results and interviews obtained, waterborne disease in the work area of the public health centre related to istewater from the Semarang East Flood Kanal. From the existing results, most of the contamination from domestic activities that do not have a istewater treatment plant and in T6 is an industrial area, which allows the contamination to come from industrial activities. Efforts are also needed to make istewater treatment installations either individually, semi-communally or communally to minimize water parameters exceeding quality standards.  Status kualitas kesehatan lingkungan yang tinggi merupakan kondisi lingkungan yang perlu dilestarikan. Kualitas kesehatan lingkungan yang buruk erat kaitannya dengan tingkat status pencemaran berat dan tingginya insiden penyakit yang ditularkan melalui air. Pada tahun 2018 terdapat 25 sungai dengan status pencemaran berat di Indonesia dan kondisi tersebut diperparah pada tahun 2019 sebanyak 38 sungai dalam kondisi status pencemaran berat. Pencemaran air dapat menjadi faktor munculnya penyakit yang ditularkan melalui air seperti diare, tifus dan leptospirosis. Penelitian ini bertujuan untuk memberikan gambaran indeks pencemaran air dan kejadian penyakit yang ditularkan melalui air pada Banjir Kanal Timur Semarang dengan pendekatan pemodelan spasial. Penelitian ini merupakan penelitian dengan pendekatan analisis spasial. Jenis data dalam penelitian ini adalah kuantitatif dengan pengambilan 6 titik sampling di tepi timur Banjir Kanal yang kemudian dianalisis dengan pemodelan spasial-Gis. Parameter indeks pencemaran air adalah total coliform, fecal coliform, oksigen terlarut, dan deterjen anionik. Dari hasil perhitungan indeks pencemaran air, titik sampel 1-6 (T1-T6) dikategorikan dengan status pencemaran ringan. Namun jika dilihat dari masing-masing parameter terdapat parameter total coliform, fecal coliform, oksigen terlarut yang melebihi baku mutu. Hasil eksisting dan wawancara yang diperoleh, waterborne disease di wilayah kerja Puskesmas terkait dengan air limbah dari Kanal Banjir Timur Semarang. Dari hasil yang ada, sebagian besar pencemaran dari kegiatan domestik yang tidak memiliki instalasi pengolahan air limbah dan di T6 merupakan kawasan industri, yang memungkinkan pencemaran berasal dari kegiatan industri. Upaya juga diperlukan untuk membuat instalasi pengolahan air limbah baik secara individual, semi-komunal maupun komunal untuk meminimalkan parameter air yang melebihi baku mutu.